Riddick collection : Pitch black ; The chronicles of Riddick [videorecording (Blu-Ray)] - Twohy, David; Wheat, Ken; Wheat, Jim; Diesel, Vin; Mitchell, Radha; Hauser, Cole, 1975-; David, Keith; Chinlund, Nick, 1961-; Griffith, Rhiana; Chung, Peter; Newton, Thandiwe, 1972-; Urban, Karl, 1972-; et al. (Universal Studios Home Entertainment, 2013)
Pitch black: Journey to a remote, hostile planet with a group of marooned passengers who learn that escaped convict Riddick isn't the only thing they have to fear.